5PSQ-028 The governance of PCSK9-inhibitors for the treatment of primary hypercholesterolaemia: appropriateness analysis. (March 2019) - Garreffa, MR; Zito, C; Esposito, S; Monopoli, C; Naturale, MD; de Francesco, AE
Abstract : Background: Recently the European Medicines Agency approved Alirocumab and Evolocumab, two monoclonal antibodies against PCSK9 (PCSK9-inhibitors), a key protein in LDL-receptor degradation. These drugs, as monotherapy or in combination with other lipid-lowering agents, represent an important therapeutic strategy in patients with high cardiovascular risk with severe familial hypercholesterolaemia or intolerance to statins. In 2017, the Regional Working Group (RWG), using the GRADE method, drafted the guidelines for the identification of the PCSK9-inhibitors prescribing centres and for the prescriptive appropriateness. Purpose: Our goal was to monitor the use of the PCSK9-inhibitors to assess the reliability of the forecasts made by the RWG and the appropriateness. Material and methods: The guidelines for appropriateness have been drawn up using the GRADE method. The data on therapeutic adherence have been extrapolated from the Health.db, appropriateness analysis tool adopted in our region since 2013. The pharmaco-utilisation data for the period January 2017 to June 2018 were obtained from the IQVIA database. Results: The pharmaceutical use data showed that about 8.6% of the regional population was treated with statins. The epidemiological evaluation using Health. db showed that the patients with high adherence to combined statin +Ezetimibe treatment were 0.2%: of these, 0.03% did not reach the therapeutic target. It is expected that only 185 patients (0.01%) present distance from the therapeutic target of more than 30% and, therefore, eligible for treatment with PCSK9-inhibitors. Also, the pharmaco-utilisation data (real data) demonstrated that the number of patients suitable for treatment with PCSK9-inhibitors in the period July2017 to June 2018 was 190, almost equal to that provided by the epidemiological analysis performed by Health.db according to the GRADE method. The use of PCSK9-inhibitors at regional level increased significantly in the first half of 2018 compared to 2017 (Δunits =+128%), probably due to the effectiveness and continuity of the treatments. Conclusion: The establishment of the RWG to define the care path for patients with high cardiovascular risk was essential for the epidemiological evaluation and monitoring of PCSK9-inhibitors therapies. This allows us to analyse the cases of suspension of therapy and the eventual occurrence of adverse events. We plan to evaluate the long-term efficacy of these treatments by observing the lowering of LDL-cholesterol. References and/or acknowledgements: 1. Grading of Recommendations Assessment, Development and Evaluation ; http://www.jclinepi.com/content/jce-GRADE-Series http://old.regione.calabria.it/sanita/allegati/dca_2017/dca_88.pdf No conflict of interest.